Can BCG vaccine protect against COVID‐19 via trained immunity and tolerogenesis?. (9th November 2020) - Basak, Preetam; Sachdeva, Naresh; Dayal, Devi
Abstract: As the number of infections and mortalities from the SARS‐CoV‐2 pandemic continues to rise, the development of an effective therapy against COVID‐19 becomes ever more urgent. A few reports showing a positive correlation between BCG vaccination and reduced COVID‐19 mortality have ushered in some hope. BCG has been suggested to confer a broad level of nonspecific protection against several pathogens, mainly via eliciting "trained immunity" in innate immune cells. Secondly, BCG has also been proven to provide benefits in autoimmune diseases by inducing tolerogenicity. Being an acute inflammatory disease, COVID‐19 requires a therapy that induces early priming of anti‐viral immune responses and regulates aberrant hyperactivity of innate‐immune cells. Here, we hypothesize that BCG can offer reliable spatiotemporal protection from COVID‐19 by triggering trained immunity and tolerogenesis, through multiple cellular pathways. We propose further research on BCG‐mediated immunoprotection, especially in vulnerable individuals, as a strategy to halt the progress of the SARS‐CoV‐2 pandemic. Also see the video abstract here https://youtu.be/P2D2RXfq6Vg. Abstract : Summary of the figure: Amidst the growing SARS‐CoV‐2 pandemic, the BCG vaccine offers a time‐tested and safe approach to control COVID‐19; that could be explored in the vulnerable subjects. As a prophylactic vaccine, BCG can induce trained immunity in innate immune cells to mount an early and effective immune response against the virus. In established COVID‐19 disease, BCG could induce tolerogenic responses to regulate hyperinflammation.